Dynamický model nové ekonomiky - Lelek, Tomáš (Univerzita Pardubice, 2009)
The paper deals with attitude to studiyng of the New Economy phenomenon. There is shift from static and individual to dynamic and system approach. The paper examines the behavior of the model. The main aim of it is to asses the significance of its individual elements. On this basis, identify the elements that are of critical for the functioning New economy and should therefore be given increased attention.
Keywords: dynamic modelling; ICT; New Economy; self-reinforcing loop